Perspectives of teachers at music schools toward children’s extra-musical abilities promoted by music lessons - Kawase, Satoshi; Kitabayashi, Yuriko (Frontiers in Psychology, 2023)
Musical activities foster children's social ability. However, the question remains whether professional music teachers consider musical training to have an influence on extra-musical abilities or only on the acquisition of musical skills. We conducted an online survey to collect open-ended responses regarding this question from over 2,000 music teachers in one of the biggest extracurricular fee-charging music school groups in Japan. Teachers' free descriptions were classified into noncognitive skills, and frequently occurring words were extracted through text mining. The results showed that, although the primary goal of music teachers who provide fee-charging lessons may be to teach musical skills to their students, they were aware of the effects of music lessons on children's non-cognitive development. Our study's main findings include: (1) despite free-descriptions, 92% of teachers reported that children acquired extra-musical abilities, and 98% of these responses were categorized as non-cognitive skills; (2) the most common responses within non-cognitive skills were "collaboration," "task performance," and "engaging with others"; and (3) there was a significant positive correlation between teaching experience and frequency of mentioning non-cognitive skills. Views on extra-musical abilities, which experienced music teachers especially had, may improve